Uterine carcinosarcoma associated with a germline nibrin (NBN) mutation - Tahireh Markert; David L. Kolin; Panagiotis A. Konstantinopoulos (Elsevier, 2022)
We report a 62-year-old patient with uterine carcinosarcoma associated with a germline mutation in the NBN gene which is involved in the homologous recombination repair (HRR) pathway. This patient responded well to several different treatment strategies including platinum-based chemotherapy twice, PARP inhibitor therapy and immunotherapy, and is currently alive and with disease control, more than four years after diagnosis. This case is the first report of uterine carcinosarcoma associated with a germline mutation in NBN and highlights how specific genomic alterations may guide treatment decisions that may alter the natural history of an otherwise devastating disease.